2022
DOI: 10.3390/ijerph19159339
|View full text |Cite
|
Sign up to set email alerts
|

Can Agricultural Productive Services Promote Agricultural Environmental Efficiency in China?

Abstract: Agricultural productive services are important paths to realize the development of green agriculture, while the effect of agricultural productive services on the agricultural environment and its influencing mechanism are not yet clear. With the panel data of agricultural production in China from 2004 to 2019, by using multi-output stochastic frontier analysis with an output-oriented distance function, this study investigates agricultural environmental efficiency based on net carbon sinks. Then, this study expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Therefore, longer-term panel data could be considered in future studies to more accurately capture the relationship between the development of AMS and the agricultural green transformation. Third, AMS exists in many aspects of agricultural production, such as tillage, sowing, irrigation, and harvesting [ 43 , 64 ]. A possible future research direction is to explore in depth the heterogeneous role of AMS in different product segments in promoting the agricultural green transformation, which will help to construct a more comprehensive AMS system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, longer-term panel data could be considered in future studies to more accurately capture the relationship between the development of AMS and the agricultural green transformation. Third, AMS exists in many aspects of agricultural production, such as tillage, sowing, irrigation, and harvesting [ 43 , 64 ]. A possible future research direction is to explore in depth the heterogeneous role of AMS in different product segments in promoting the agricultural green transformation, which will help to construct a more comprehensive AMS system.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al characterized agricultural services in terms of agricultural services output and indicated that agricultural services helped to promote the growth of AGTFP, and the improvement effect was higher in the eastern region [ 42 ]. Zhu et al characterized productive agricultural services in terms of the number of people employed in agricultural services and indicated that productive agricultural services effectively improved agri-environmental efficiency by optimizing inputs and increasing outputs [ 43 ]. From a micro perspective, Li et al showed that adopting green agricultural services by farmers helped improve AGTFP, and the improvement effect was more substantial with higher adoption [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…One way to solve the dilemma of the weak income increase of farmers is to promote the agricultural division of labor. Agriculture "imports" the division of labor economy from industry through the purchase of machinery and the indirect production effect, which greatly extends the space of the specialized division of labor and the trade radius [25], thus generating an agricultural machinery socialization service and improving production efficiency [26]. The adoption of agricultural machinery socialization In general, there have been discussions on the relationship between agricultural machinery socialization services and the relative poverty of farmers, which has laid a good foundation for the smooth development of this study.…”
Section: Impact Of Agricultural Machinery Socialization Service Adopt...mentioning
confidence: 99%
“…On the other hand, the adoption of agricultural machinery socialization services by farmers adds mechanical elements to agricultural production, and the mechanical operation efficiency is generally higher than that of manual operations, thus improving agricultural production efficiency. At the same time, the adoption of agricultural machinery socialization services can accelerate the non-agricultural transfer of labor by promoting the improvement of labor allocation efficiency [25], increasing the wage income of farmers, and alleviating relative poverty. In addition, agricultural machinery socialization services will embed other production factors such as pesticides and fertilizers into the production process so that farmers can obtain other production factors more conveniently, reduce transaction costs, and alleviate relative poverty [27].…”
Section: Impact Of Agricultural Machinery Socialization Service Adopt...mentioning
confidence: 99%
“…Ji (2018) concluded that APS significantly reduce pesticide use and enhance pesticide abuse prevention and control [35]. Zhu et al (2022) concluded that APS effectively improve agro-environmental efficiency by optimizing the input-output structure [36].…”
Section: Introductionmentioning
confidence: 99%